Pengembangan Website Sekolah di Sd Negeri 2 Sukatani (Current Research in Education: Conference Series Journal, 2023)
The development of information technology is also developing in line with the development of human civilization. Advances in technology have made the world of education have an impact, especially in the dissemination of information, now many schools have websites. However, SD Negeri 2 Sukatani still uses manual methods and information dissemination so that information data is still difficult to obtain. In this study, research and development was carried out with an agile scrum development model where data were obtained from the results of research, observation, and interviews conducted with educators, then qualitative data analysis was carried out by reducing data, presenting data, and drawing conclusions. Based on the results of this research analysis will develop a school website with the aim that information can be more easily obtained. This study uses a qualitative agile development method with a scrum model consisting of three stages, namely pre-game, game, and post-game. The website that was built has nine pages with their respective functions. From this research it can be concluded that the website that was built can help the process of disseminating information to be more efficient and the website that has been developed is running well but still needs further development.